EFEKTIVITAS STRATEGI PEMBELAJARAN CULTURALLY RESPONSIVE TEACHING (CRT) DALAM MENINGKATKAN HASIL BELAJAR PJOK KELAS X DI SMA NEGERI 2 SEMARANG - Hendrawan, Burhan; Hinda Zhannisa , Utvi; Lukas Waskitho , Tutur (Journal of Physical Activity and Sports (JPAS), 2024)
Physical education, sports, and health is part of the school curriculum and includes a variety of materials. The objective of the Classroom Action Research titled "Efforts to Improve iPJOK Learning Relevant to the Needs of Class X-10 Students at SMA Negeri 2 Semarang" is to enhance students' learning outcomes. The main objective of this research is to improve students' academic performance in the subject of PJOK. By identifying relevant learning approach strategies, it is hoped that students can achieve a better understanding, enhance concept mastery, and attain higher achievements in PJOK. This survey research focuses on students as the object of study, with the aim of improving PJOK learning. The research was conducted on 36 students from class X-10 at SMA Negeri 2 Semarang. It can be iobserved that after the intervention, the learning outcomes of the X-10 class students were declared complete, with the highest results achieved ithrough the CRT approach, involving 24 students. This ishows ithat ithe percentage of success of the most effective learning strategy using student strategies has achieved overall classical completeness. Thus, it can be concluded that the use of the CRT approach in learning can enhance the active engagement of students in class X-10 at SMA iN 2 Semarang.